A detailed look at the Fed's crisis response by funding facility and recipient - James Andrew Felkerson (Levy Economics Institute of Bard College, 2012)
The extraordinary scope and magnitude of the financial crisis of 2007-09 required an extraordinary response by the Federal Reserve in the fulfillment of its lender-of-last-resort (LOLR) function. In an attempt to stabilize financial markets during the worst financial crisis since the Great Crash of 1929, the Fed engaged in loans, guarantees, and outright purchases of financial assets that were not only unprecedented, but cumulatively amounted to over twice current US GDP as well. the purpose of this brief is to provide a descriptive account of the Fed's response to the recent crisis - to delineate the essential characteristics and logistical specifics of the veritable "alphabet soup" of LOLR machinery rolled out to save the world financial system. It represents the most comprehensive investigation of the raw data to date, one that draws on three discrete measures: the peak outstanding commitment at a given point in time; the total peak flow of commitments (loans plus asset purchases), which helps identify periods of maximum financial system distress; and, finally, the total amouunt of loans and asset purchases made between January 2007 and March 2012. This third number, which is a cumulative measure, reveals that the total Fed response exceeded 29 trillion. Providing this account from such varying angles is a necessary first step in any attempt to fully understand the actions of the central bank in this critical period - and a prerequisite for thinking about how to shape policy for future crises.
Keywords: 330